PENGARUH TINGKAT SUKU BUNGA KREDIT TERHADAP LABA PADA PT BANK RAKYAT INDONESIA (PERSERO) Tbk. UNIT MANGGALA MAKASSAR - Ibrahim Ibrahim (AkMen JURNAL ILMIAH, 2016)
This study aims to determine the effect of the interest rate of credit to profit at PT Bank Rakyat Indonesia (Persero) Tbk Unit Mangala Makassar). This study uses secondary data reporting changes in income and interest rates from Bank BRI Unit Mangala in Makassar. Data were analyzed with descriptive quantitative method, then used a simple linear regression analysis model to see the effect of the interest rate on profits. The results showed that 1. Factors interest rate effect on profit at PT Bank Rakyat Indonesia (Persero), Tbk Unit Mangala in Makassar. 2. The decline in mortgage interest rates will not mean lower profits, but instead raise bank.3 profit. Increased lending rates will allow a decrease in profit, due to high lending rates.